Analisis Ekspresi Protein TLR-9, CD90 dan VEGF pada Mesenchymal Stem Cell di Jaringan Tumor Osteosarkoma - Hernanda, Pratika Yuhyi (Universitas Wijaya Kusuma Surabaya, 2019)
For further investigation on the effect of Mesenchymal Stem Cell (MSC) on tumor / cancer growth, it is necessary to start with tumor MSC profile from tumor / cancer tissue. In this study, we use MSC from osteosarcoma tissue as a representative. The MSC profile analysis method used were the comparing the phenotype and characteristics of MSC fromosteosarcoma tissue with MSC from normal adiposa tissue. The characteristics of MSC were represented by protein expression of several candidate genes namely TLR-9, CD-90 and VEGF. From the results of immunofluorescence staining on adiposa MSC compared withosteosarcoma MSC, it has obviously seen that although the phenotypes were similar, there was no significant difference in CD-90 expression in osteosarcoma MSC and adiposa MSC. Although VEGF expression appears to be slightly prominent in osteosarcoma MSCs, the difference between the two was also not significant. Whereas TLR9 expression is very prominent in osteosarcoma MSC and significantly different from adiposa MSC. Thus TLR9 may be of concern in subsequent studies to investigate the mechanism of MSC triggers tumor growth.